Design Of A Quasi-Lumped Element Resonator Antenna With Magnetic Coupling Feeding - Olokede, Seyi Stephen (2013)
Advancement in wireless systems and subsequent increasing demand in wireless mobility has enabled the invention of the wearable wireless systems. Realizing this fact, lightweight, conformable, unobtrusive, and ubiquitous equipment, which can be integrated into everyday use, are now crucial design considerations. These wireless communication systems contain several parts in which compact antennas are an essential subpart. However, many technical challenges arise in designing robust, compact and efficient antennas that deliver the necessary performance to support the emerging applications. Limitations due to electrical length, low radiative resistance, high Q-factor, narrow bandwidth, feeding difficulties are among the numerous challenges confronting the feasibility of designing small antennas. Therefore, the intent of this work is to develop an alternative antenna structure that meets the compact requirements in terms of size, without compromising the antenna radiation characteristics. Three antenna designs configurations are developed. The first design is a simple single quasi-lumped element resonator antenna arrangement which was excited by a coaxial feed probe. The antenna structure was photo-edged on a Duroid RO4003C with a permittivity of 3.38 and thickness of 0.813 mm. The size of the resonator is 5.8×5.6 mm2 with conductor thickness of 0.035 mm. The simulation, fabrication, and measurement were conducted to ascertain its performance characteristics thereby validating the inherent potential of the proposed resonator as an antenna candidate. The design and radiation equations were presented. Based on the performance of the first configuration, a 6-element series array quasi-lumped element resonator antenna and the rectangular planar array were designed, fabricated and measured. The latter configuration was excited by the coaxial feed probe, whereas the former was fed by a microstrip-line and excited with a coaxial feed probe.